Topical 15% Paromomycin-Aquaphilic for Bolivian Leishmania braziliensis Cutaneous Leishmaniasis: A Randomized, Placebo-controlled Trial. (27th September 2018) - Soto, Jaime; Soto, Paula; Ajata, Andrea; Luque, Carmelo; Tintaya, Carlos; Paz, David; Rivero, Daniela; Berman, Jonathan
Abstract: Background: Cutaneous leishmaniasis (CL) presents as 1 or more skin lesions, which makes local therapy inherently attractive compared to systemic therapy that exposes the whole body to a drug. For 30 years, 15% paromomycin topical formulations have been in clinical experimentation. Recently, 15% paromomycin in Aquaphilic, a complex base to facilitate adsorption into the lesion, was found superior to aquaphilic vehicle for Old World Leishmania major disease. Methods: We performed a randomized trial of 15% paromomycin in Aquaphilic (40 patients) vs Aquaphilic vehicle (20 patients) vs a positive control (intralesional pentamidine; 20 patients) against L. braziliensis CL in Bolivia Results: Cure rates after 6 months of follow-up were 31 of 40 (77.5%, 95% confidence interval [CI] 62.5–88%) for paromomycin-Aquaphilic, 2 of 20 (10%, 95% CI 3–30%) for Aquaphilic vehicle ( P < .0001 vs paromomycin-Aquaphilic), and 14 of 20 (70%, 95% CI 48–85.5%) for intralesional pentamidine. Both paromomycin-Aquaphilic and the Aquaphilic vehicle were very well tolerated, with only grade 1 adverse reactions in 5–10% of patients. Conclusions: Against L. braziliensis CL, a prevalent, aggressive form of New World CL, 15% paromomycin-aquaphilic was vastly superior to a negative vehicle control and was comparable in efficacy to a positive control. This study enlarges the potential use of 15% paromomycin-Aquaphilic from one form of Old World CL to CL more generally. Clinical Trials Registration: NCT03096457. Abstract : Topical application of 15% paromomycin in Aquaphilic cured 77.5% of 40 patients with Bolivian Leishmania braziliensis cutaneous leishmaniasis, compared to 10% of 20 patients randomized to placebo (Aquaphilic). This suggests that paromomycin-Aquaphilic has a role for New World cutaneous leishmaniasis.